Exploring the educational needs of patients with cutaneous lymphoma using an educational needs assessment tool - Ivert, Lina U.; Winther, Anna H.; Jonsson, Pontus; Brauner, Hanna (Frontiers in Oncology, 2024)
Background: Cutaneous T-cell lymphomas (CTCL) are a group of rare non-Hodgkin lymphomas characterized by initial localization of malignant T-lymphocytes in the skin. Support and information from nurses and patient support groups have proven useful for patients with CTCL, but little is known about the educational needs of these patients.To investigate the self-reported educational needs among CTCL patients using an educational needs assessment tool and to explore differences related to sex, age, disease duration, clinical stage, and education.Methods: This observational single center study analyzed 70 patients with CTCL in routine dermatological outpatient care. The patients were asked to complete a questionnaire to capture their educational needs in regard to CTCL. The questionnaire was inspired by the educational needs assessment tool, designed and validated for patients with rheumatoid disease. The questionnaire included a general question, "In general, how much information do you want to receive about your lymphoma disease?", and five domains covering information relating to disease process (6 items), treatment (4 items), feelings (2 items), self-management of itch, sleep, and rest (2 items), and support systems (3 items). The domain scores ranged from 0 to 18 and the total score from 0 to 51, with a higher score indicating a greater need for education.Results: When asked "In general, how much information do you need?", females wanted to know more compared with males (2.6 vs. 2.1, p=0.006), and patients with higher education wanted to know more than patients with lower education (2.5 vs. 2.0, p=0.025). The domains concerning treatment (80%) and disease process (75%) revealed the greatest needs for education. Patients with a disease duration <2 years reported a greater educational need for the domain support system, compared with patients with longer disease duration. Patients with lower education reported a greater educational need about feelings compared with patients with higher education.We found that 65% of the CTCL patients in the cohort, particularly females, expressed a need for education, especially regarding disease process and treatment. A deeper understanding of the educational needs would enable healthcare providers to give personalized information.